STRATEGI PETANI DI SEKITAR TAMBANG EMAS - Gusti Putu Sawantara; Sarlan Adijaya (KABANTI : Jurnal Kerabat Antropologi, 2022)
This study aims to determine and describe the condition of the farming community in Kalaero Village, Lantari Jaya District, Bombana Regency. To analyze the data in this study, the adaptation theory of John William Benneet was used. The data collection technique used is a field research technique using two methods, namely observation and indepth interviews. This research is a qualitative research and uses ethnographic methods. The environmental changes caused by mining include (1) changes in the landscape (2) reduced water discharge (3) silting of rivers and dams (4) silting of agricultural irrigation (5) changes in agricultural soil fertility. Then the ways for the community to deal with the problems caused by mining activities include (1) planting other commodities other than lowland rice (2) changing the planting chart (3) increasing the use of fertilizers (4) blinding drilled wells for irrigating rice fields (5) conducting loans for capital (6) expand arable land. All of that is a form of farmers' efforts to maintain their agriculture.